The Date of the Bucolic Poet Martius Valerius*. (6th September 2017) - Stover, Justin A.
ABSTRACT: The collection of four Latin bucolics ascribed to one Martius Valerius was only published in the twentieth century; they have been widely considered as twelfth-century compositions. Picking up on suggestions proposed by François Dolbeau, this study presents evidence that Martius drew directly on the bucolics of Theocritus, and that his poems are late antique, not medieval, literary productions, probably written in the sixth century. Such a conclusion will require a revision of the history of post-Virgilian Latin bucolic poetry.